Performance improvement of simplified synchronous generators using an active power filter - Abu-Jalala, Al-Hussein; Cox, Tom; Gerada, C.; Rashed, Mohamed (2017)
Active power filters (APF) are used to improve power quality and are commonly connected in parallel with the load at the point of common coupling (PCC). They are used to compensate for harmonics from nonlinear loads, for reactive power compensation and/or balancing mains currents. This paper will investigate the effect of using an APF to improve the output power quality of a simplified synchronous generator (SSG) with distorted back-EMF. The work will further investigate the use of an APF in parallel to improve the transient response of synchronous generator without damper bars, in order to control the dynamic response from a sudden change in the connected load. Using an APF, simulation results show significant improvements in both generator output current quality and transient response to load step changes without damper bars.